Reciprocity Across Modes of Supply in the World Trade Organization : A Negotiating Formula - Mattoo, Aaditya; Olarreaga, Marcelo (World Bank, Washington, DC, 2014)
Negotiations on trade in services at the World Trade Organization (WTO) have so far produced little liberalization beyond levels countries have undertaken unilaterally. One reason: limited application of the traditional negotiating principle of reciprocity. In particular, participants have failed to exploit the scope of the services agreement (General Agreement on Trade in Services -GATS) for the exchange of market-access "concessions" across different modes of supply - cross-border delivery and the movement of capital and workers. Using the Heckscher-Ohlin-Vanek framework, the authors propose a negotiating formula that generalizes the fundamental WTO principle of reciprocity to include alternative modes of delivery. Adoption of this formula as a basis for negotiations could bring greater commitments to liberalization on all modes of delivery, producing substantial gains in global welfare and more balanced outcomes.